Improving Instructional Simulation With Structural Debriefing. (June 2015) - Pavlov, Oleg V.; Saeed, Khalid; Robinson, Lawrence W.
Background. Research shows that learning and task performance improve when participants in management exercisesunderstand the structure of the system theycontrol . However, the majority of business simulators are black-boxes . Aim. This article introducesstructural debriefing, which is a debriefing activity aimed at helping students learn aboutcausal relationships, feedbacks, accumulations, anddelays within a black-box simulation. Method. A structural debriefing can be prepared and facilitated by following theStructural Debriefing Protocol . Results. Apilot study was conducted in which undergraduate students participated in a structural debriefing of The LITTLEFIELD TECHNOLOGIES, a popular simulation for teaching principles of operations management. The students were able to complete all eight steps of a structural debriefing, but required considerabletime (three academic terms) to do so. Not every instructional simulation will require all the steps or such a large time commitment. Conclusion. The successful completion of the pilot study demonstrates thatstructural debriefing is auseful debriefing technique. However, to be effective, the scope and format of a structural debriefing activity must suitpractical andpedagogical considerations.